Initial disease course and treatment in an inflammatory bowel disease inception cohort in Europe: the ECCO-EpiCom cohort - Burisch, Johan; Pedersen, Natalia; Cukovic-Cavka, Silvja; Turk, Niksa; Kaimakliotis, Ioannis; Duricova, Dana; Shonová, Olga; Vind, Ida; Avnstrøm, Søren; Thorsgaard, Niels; Krabbe, Susanne; Andersen, Vibeke; et al. (Inflammatory bowel diseases, 2014)
BACKGROUND: The EpiCom cohort is a prospective, population-based, inception cohort of inflammatory bowel disease (IBD) patients from 31 European centers covering a background population of 10.1 million. The aim of this study was to assess the 1-year outcome in the EpiCom cohort. METHODS: Patients were followed-up every third month during the first 12 (±3) months, and clinical data, demographics, disease activity, medical therapy, surgery, cancers, and deaths were collected and entered in a Web-based database (www.epicom-ecco.eu). RESULTS: In total, 1367 patients were included in the 1-year follow-up. In western Europe, 65 Crohn's disease (CD) (16%), 20 ulcerative colitis (UC) (4%), and 4 IBD unclassified (4%) patients underwent surgery, and in eastern Europe, 12 CD (12%) and 2 UC (1%) patients underwent surgery. Eighty-one CD (20%), 80 UC (14%), and 13 (9%) IBD unclassified patients were hospitalized in western Europe compared with 17 CD (16%) and 12 UC (8%) patients in eastern Europe. The cumulative probability of receiving immunomodulators was 57% for CD in western (median time to treatment 2 months) and 44% (1 month) in eastern Europe, and 21% (5 months) and 5% (6 months) for biological therapy, respectively. For UC patients, the cumulative probability was 22% (4 months) and 15% (3 months) for immunomodulators and 6% (3 months) and 1% (12 months) for biological therapy, respectively in the western and eastern Europe. DISCUSSION: In this cohort, immunological therapy was initiated within the first months of disease. Surgery and hospitalization rates did not differ between patients from eastern and western Europe, although more western European patients received biological agents and were comparable to previous population-based inception cohorts.
Keywords: indukce remise; dospělí; Prognosis; Prospective Studies; senioři nad 80 let; Databases, Factual; Humans; databáze faktografické; následné studie; lidé středního věku; prospektivní studie; Aged, 80 and over; Middle Aged; Young Adult; Europe; mladý dospělý; Combined Modality Therapy; prognóza; Follow-Up Studies; incidence; Remission Induction; mužské pohlaví; Adult; Inflammatory Bowel Diseases; Disease Progression; Adolescent; Evropa; kombinovaná terapie; idiopatické střevní záněty; ženské pohlaví; lidé; mladiství; Incidence; Aged; senioři; progrese nemoci; Male; Female